Dukungan Teknologi Informasi Pada Proses Bisnis Pada Usaha Kecil Dan Menengah (Studi pada Industri UKM di Bangunjiwo, Kasihan, Bantul) - Agus Sukarno; Tri Wahyuningsih; Yuli Liestyana (Universitas Muhammadiyah Yogyakarta, 2013)
This study aims to analyze how well IT is used to support the business processes of SMEs in Bangunjiwo, and to identify ways to help SMEs improve IT support for business processes in SMEs in Bangunjiwo. This research is expected to have benefits that can increase managers/owners awareness to take advantage of the information technology support in business processes. By knowing the results of this study, the SMEs are expected to further improve the use of information technology in business processess as to achieve competitive advantage.The unit of analysis for this study is the SME organization, so every organization represented by one person (owner or manager). Population of the research is small and medium companies in Bangunjiwo, Kasihan, Bantul. The sample was selected using purposive sampling technique to determine which companies will be the respondent.The results show that IT support for each business process is lower than importance level that business processes run bySMEs in Bangunjiwo. IT support for SMEs in the business process can be enhancedby the disseminationof research results to the SMEs in Bangunjiwo, so they can understand the importance of IT support. Socialization is intended to motivate the use of IT facilities economically an deasily, so it can be done by SMEs.